2019
DOI: 10.1111/medu.13886
|View full text |Cite
|
Sign up to set email alerts
|

Student and clinician identities: how are identities constructed in interprofessional narratives?

Abstract: CONTEXT Although the literature on professional identity formation in medical education is increasing, it is scant by comparison on student and clinician identities within interprofessional contexts. We therefore adopt a novel discursive approach to identities to explore how soon-to-become graduates and workplacebased clinicians construct their own and others' identities in interprofessional student-clinician (IPSC) interaction narratives. METHODS We conducted a qualitative narrativeinterview study with 38 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 52 publications
1
46
0
1
Order By: Relevance
“…However, other articles 45,48,51,55‐57,66,68,71,77,83,95,99‐104 described the impact of relationships on PIF, which was occasionally evidenced in trainees’ discourses 56,75 . These articles underscore how identity construction occurs in relation to others and never in isolation 57 .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…However, other articles 45,48,51,55‐57,66,68,71,77,83,95,99‐104 described the impact of relationships on PIF, which was occasionally evidenced in trainees’ discourses 56,75 . These articles underscore how identity construction occurs in relation to others and never in isolation 57 .…”
Section: Resultsmentioning
confidence: 97%
“…Grounded theory (n = 17) was cited as the most commonly used methodology, which is appropriate in contexts in which researchers believe divergent epistemologies exist 69 . However, quite a few studies did not mention their choice of methodology (n = 11) and reported vague terms such as ‘inductive analysis’ or ‘open coding’ to describe the analytical work 45,51,52,54,55,58,63‐65,70‐81 . Studies included various contexts previously identified in health education research 82 (eg, longitudinal clerkships, social media, patient care, dual professions, etc.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on clinicians’ identity formation has largely used post‐event data from interviews 18,19 and reflective diaries 10 . To understand the social dynamics of identity formation, contemporaneous naturalistic data is needed 20 .…”
Section: Introductionmentioning
confidence: 99%